1999
DOI: 10.1677/jme.0.0230277
|View full text |Cite
|
Sign up to set email alerts
|

Complex mediation of uterine endometrial epithelial cell growth by insulin-like growth factor-II (IGF-II) and IGF-binding protein-2

Abstract: The coexpression of IGF (-I and -II) peptides, corresponding receptors, and IGF binding proteins (IGFBPs) in uterine endometrium suggests that a significant component of IGF action in this tissue is via autocrine or paracrine pathways, or both. The present study examined whether IGF-II and a major uterine-expressed IGF-II binding protein, IGFBP-2, modulate endometrial epithelial cell mitogenesis. Serum-deprived porcine endometrial glandular epithelial (GE) cells of early pregnancy were treated with various con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Further, it was proposed that the mitogenic effect of IGFBP-2 may be IGF independent. 18,19 More recently, IGF-independent actions of IGFBP-2 have been recognized. For example, IGFBP-2 stimulated the proliferation of human epithelial ovarian cancer cells and activated the extracellular signal regulated kinase (ERK1=2) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was proposed that the mitogenic effect of IGFBP-2 may be IGF independent. 18,19 More recently, IGF-independent actions of IGFBP-2 have been recognized. For example, IGFBP-2 stimulated the proliferation of human epithelial ovarian cancer cells and activated the extracellular signal regulated kinase (ERK1=2) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the IGFBP transport functions, IGFBPs are involved in cell cycle, apoptosis, cell adhesion and motility in various tissues [32,33]. IGFBP expression in the uterus is highly associated with IGF-I activity [34][35][36]. In the human endometrium, the expression of mRNAs for the six IGFBPs are detected during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in several cell culture models, addition of IGFBPs to cell culture medium is able to inhibit IGF-I and IGF-II action, but not or only partially the action of analogs of IGF-I (LongR3-IGF-I, Des1-3-IGF-I, [QAYL]-IGF-I) that bind weakly to IGFBPs [2][3][4][5][6]. However, it has been shown that IGFBP-2, -3 and -5 can also potentiate IGF actions possibly by their ability to bind to the extracellular matrix, which induces a reduction of their affinity for IGFs [7,8]. Potentiating effects on IGF action can also be the consequence of the proteolytic degradation of IGFBPs that results in a strong reduction in their affinity for their ligands [9][10][11].…”
Section: Introductionmentioning
confidence: 99%